Rencana Pengembangan Bisnis Kesehatan (Studi Pada Rumah Sakit XYZ) - Puspa, Cicilia Dian; Suwandi, Dr; Verdiana, Cornelia; Derifisharity, Friskha; Ramadhani, Indah Trian; Ayu, Ni Made Dhiyah; Fauzi, Rico Achmad; Fatimah, Siti Furqonti (Journal of Entrepreneurship, Management and Industry (JEMI), 2020)
Abstract This business plan aims to make it easier to run a business by knowing practical steps in dealing with competition, promotions, and etc., to be more effective and profitable, easier business supervision, and as material for strategy development and business evaluation. This business plan uses SWOT analysis, Segmentation, Targeting, and Positioning analysis, and Marketing Mix analysis. This business plan explains how XYZ Hospital develops business through Telemedicine XYZ (t-XYZ) to improve the quality of hospital services. This business development plan is projected to get annual profits that always increase, with a payback period of less than one year, NPV values ​​more than zero or positive, and the profitability index value more than zero or 3.4. With these criteria, the business plan is feasible and profitable to run. Keywords: Business plan, Telemedicine, SWOT, STP, Marketing mix. Abstrak Rencana bisnis ini bertujuan untuk mempermudah dalam menjalankan bisnis dengan mengetahui langkah-langkah praktis menghadapi persaingan, promosi, dan lain-lain agar lebih efektif dan menguntungkan, mempermudah pengawasan bisnis, dan sebagai bahan untuk pengembangan strategi dan evaluasi bisnis. Rencana bisnis ini menggunakan analisis SWOT, Segmentasi, Penargetan, dan analisis Positioning, dan analisis Bauran Pemasaran. Rencana bisnis ini menjelaskan bagaimana Rumah Sakit XYZ mengembangkan bisnis melalui Telemedicine XYZ (t-XYZ) untuk meningkatkan kualitas layanan rumah sakit. Rencana pengembangan bisnis ini diproyeksikan untuk mendapatkan laba tahunan yang selalu meningkat, dengan waktu pengembalian kurang dari satu tahun, nilai NPV lebih dari nol atau positif, dan nilai indeks profitabilitas lebih dari nol atau 3,4. Dengan kriteria ini, rencana bisnis layak dan menguntungkan untuk dijalankan. Kata kunci: Rencana bisnis, Telemedicine, SWOT, STP, Bauran Pemasaran.